2008
DOI: 10.1136/bjo.2008.144584
|View full text |Cite
|
Sign up to set email alerts
|

Visual and medical risk factors for motor vehicle collision involvement among older drivers

Abstract: Aims-To identify visual and medical risk factors for motor vehicle collisions (MVCs).Methods-Data from four cohorts of older drivers from three states were pooled (n=3,158). Health information was collected at baseline, and MVC data were obtained prospectively. Cox proportional hazards regression was used to estimate rate ratios (RRs) and 95% confidence intervals (CIs) for associations between medical characteristics and MVCs.Results-A total of 363 MVCs were observed during the study period (1990-1997), of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 21 publications
(31 reference statements)
6
110
3
Order By: Relevance
“…Both case-control studies and prospective cohort studies have often been limited by failure to control for driving exposure or mileage (e.g., Selzer et al 1968;Selzer and Vinokur 1975), low response rates or sample sizes (e.g., Hilton et al 2009;Sagberg 2006;Sims et al 2000), neglecting less serious collisions (e.g., Koepsell et al 1994;Wilk 2007, 2012;Margolis et al 2002;Marottoli et al 1994), possible underreporting of both collisions and psychiatric conditions due to reliance on selfreport (e.g., Cross et al 2009;Mann et al 2010;Sagberg 2006;Wickens et al 2013), and the use of numerous statistical tests that may have resulted in some associations occurring by chance alone (e.g., Koepsell et al 1994;Sims et al 2000). Perhaps due in part to these limitations, the results of these studies have been inconsistent; however, there does appear to be some evidence that depression is associated with increased collision risk.…”
Section: Increased Collision Riskmentioning
confidence: 99%
“…Both case-control studies and prospective cohort studies have often been limited by failure to control for driving exposure or mileage (e.g., Selzer et al 1968;Selzer and Vinokur 1975), low response rates or sample sizes (e.g., Hilton et al 2009;Sagberg 2006;Sims et al 2000), neglecting less serious collisions (e.g., Koepsell et al 1994;Wilk 2007, 2012;Margolis et al 2002;Marottoli et al 1994), possible underreporting of both collisions and psychiatric conditions due to reliance on selfreport (e.g., Cross et al 2009;Mann et al 2010;Sagberg 2006;Wickens et al 2013), and the use of numerous statistical tests that may have resulted in some associations occurring by chance alone (e.g., Koepsell et al 1994;Sims et al 2000). Perhaps due in part to these limitations, the results of these studies have been inconsistent; however, there does appear to be some evidence that depression is associated with increased collision risk.…”
Section: Increased Collision Riskmentioning
confidence: 99%
“…65 " The useful field of view becomes smaller in older adults when distractions are present, making visual search less efficient. Cross and colleagues 160 report that a greater than 35% reduction in UVOF is significantly associated with an increased rate of motor vehicle collisions (MVCs) in a three-state cohort of older drivers. This same study found that there was no association between visual acuity and contrast sensitivity in older adults and MVC involvement.…”
Section: Drivingmentioning
confidence: 98%
“…However, studies using a range of sample sizes and methodologies have found only a weak relationship between VA and crash risk (Hofstetter, 1976;Gresset and Meyer, 1994;Marottoli, 1998;Ivers et al, 1999) or no association (Keeffe et al, 2002;Rubin et al, 2007;Cross et al, 2009). High-contrast static VA is unlikely to represent the normal-driving environment that includes both static and moving objects of different sizes and contrast levels.…”
Section: Visual Functionmentioning
confidence: 99%